Quantum dot ink for printing optical materials and preparation method thereof

By treating lignin under high temperature and high pressure conditions, and adding nano alumina dispersion and sodium hypochlorite solution to the hydrothermal reaction, the problem of difficult regulating the properties of lignin carbon quantum dots in traditional quantum dot inks is solved, and the precise regulation of product performance and consistency of performance between different batches is achieved.

CN119875422AInactive Publication Date: 2025-04-25SHENZHEN CHENGYUXING PHOTOELECTRICITY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510132126.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In traditional quantum dot inks, when lignin carbon quantum dots are used as raw materials, it is difficult to accurately regulate the properties of lignin quantum dots, resulting in the inability to accurately regulate product performance, and the performance differences between different batches are large.

Method used

After mixing dealkaline lignin with water, insulation and pressure is carried out under high temperature and high pressure conditions, and then instantly relieves pressure to obtain blasting material. Then, a nano-alumina dispersion and sodium hypochlorite solution were added to the hydrothermal reaction, and after shear dispersion and hydrothermal reaction, the nano-alumina was removed by pickling and dialysis to obtain lignin carbon quantum dots.

Benefits of technology

It realizes precise regulation of the properties of lignin carbon quantum dots, improves the consistency of product performance and fluorescent quantum yield, and is suitable for the preparation of printed optical materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005261928100000081
    Figure BDA0005261928100000081
  • Figure BDA0005261928100000091
    Figure BDA0005261928100000091
Patent Text Reader

Abstract

The invention belongs to the technical field of optical ink. The invention relates to the field of ink, in particular to quantum dot ink for printing optical materials and a preparation method thereof. The preparation method comprises the following specific preparation steps: preparing lignin carbon quantum dots: mixing dealkalized lignin and water, standing for swelling, keeping the temperature and the pressure under the conditions that the pressure is 6.0-8.0 MPa and the temperature is 180-220 DEG C, and instantaneously releasing the pressure to normal pressure to obtain a blasting material; ultrasonically dispersing nanometer aluminum oxide particles in water to obtain nanometer aluminum oxide dispersion liquid; uniformly shearing and dispersing the blasting material and the nano aluminum oxide dispersion liquid, carrying out hydrothermal reaction for 10-12 hours at the temperature of 180-200 DEG C, after the reaction is finished, carrying out acid pickling to dissolve and remove nano aluminum oxide, then filtering, dialyzing and drying to obtain the lignin carbon quantum dots, and preparing the ink: uniformly dispersing the lignin carbon quantum dots, the solvent and the binder to obtain the quantum dot ink for printing the optical material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of optical inks, and more specifically, relates to a quantum dot ink for printing optical materials and a preparation method thereof. Background Art

[0002] Since their discovery, carbon quantum dots have been widely used in biomedicine, fluorescent probes and electrochemical energy due to their excellent chemical stability, low toxicity, fluorescence, optical stability, wide range of raw materials and low cost.

[0003] Among traditional fluorescent anti-counterfeiting inks, photochromic inks are favored because of their green and non-toxicity, fine base color, fast drying, and thin ink layer. However, the manufacturing cost of photochromic inks is high, and their light-changing or fluorescent effects are not ideal. Moreover, the fluorescent effect they present under the action of external excitation light is greatly limited by the structure, performance, and dosage of fluorescent fillers. Compared with traditional fluorescent fillers formed by metal frames or rare earth elements and organic compounds, carbon quantum dots have the advantages of more regular particle size, low toxicity, good fluorescence effect, wide carbon source source, and simple preparation process. They have broader application prospects as fluorescent fillers for preparing fluorescent anti-counterfeiting inks. The carbon source precursors of carbon quantum dots mainly include two categories. One is non-biomass carbon source materials, such as cobalt phthalocyanine and other materials, but most of the carbon quantum dots prepared from such raw materials have strong toxicity; the other is biomass carbon source materials that are more widely distributed in nature than non-biomass carbon source materials, and the carbon quantum dots prepared from such materials have low toxicity. Lignocellulose is a typical biomass carbon source precursor material. Compared with cellulose and hemicellulose, lignin has the lowest utilization rate.

[0004] However, at present, the bottleneck problem that still exists is: the chemical structure of lignin is complex, containing a variety of CO and CC bonds, and the strength range of these bonds is relatively wide, resulting in multiple chemical changes in the depolymerization process of lignin, complex influencing factors, and it is difficult to accurately control the chemical composition, size and properties of the product. In particular, during the preparation process, lignin often needs to be doped. Heteroatom doping can regulate the excitation-dependent luminescence behavior of carbon quantum dots, but there is currently a lack of effective control methods for the heteroatom doping process of lignin-based carbon quantum dots, making it difficult to achieve precise regulation of their luminescence behavior. Summary of the invention

[0005] The technical problem to be solved by the present invention is that, in traditional quantum dot inks, when lignin carbon quantum dots are used as raw materials, it is difficult to precisely control the properties of lignin quantum dots during the preparation process, resulting in the inability to precisely control product performance and large performance differences between different batches. Based on the above difficulties, the present invention provides a quantum dot ink for printing optical materials and a preparation method thereof.

[0006] The purpose of the present invention is to provide a method for preparing quantum dot ink for printing optical materials.

[0007] Another object of the present invention is to provide a quantum dot ink for printing optical materials.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing quantum dot ink for printing optical materials, the specific preparation steps comprising:

[0010] Preparation of lignin carbon quantum dots:

[0011] After the dealkalized lignin and water are mixed, they are allowed to stand and swell, and then they are kept at a pressure of 6.0-8.0MPa and a temperature of 180-220°C, and then the pressure is instantly released to normal pressure to obtain a blasting material;

[0012] By keeping the temperature and pressure under high temperature and high pressure, under this condition, the high-pressure steam penetrates into the lignin and destroys the lignin structure, causing the dealkalized lignin to soften, the connection strength to decrease, and even become plastic. After instantaneous pressure relief, the high-pressure steam inside the lignin fiber further defibrates the lignin fiber due to the instantaneous change in pressure, fully stretching and exposing its molecular chain active functional groups;

[0013] Ultrasonic dispersion of nano-alumina particles in water to obtain a nano-alumina dispersion;

[0014] After the blasting material and the nano-alumina dispersion are evenly dispersed by shearing, the reaction is carried out at a temperature of 180-200°C for 10-12 hours. After the reaction is completed, the nano-alumina is dissolved and removed by acid washing, and then filtered, dialyzed, and dried to obtain lignin carbon quantum dots.

[0015] Ink preparation:

[0016] The lignin carbon quantum dots, solvent and binder are evenly dispersed to obtain quantum dot ink for printing optical materials.

[0017] The beneficial effects brought by the above technical solution are:

[0018] The above technical solution uses nano-alumina dispersion and blasting material for shear dispersion. During the dispersion process, the active functional groups of the lignin molecular chains that are fully stretched during the blasting process can be adsorbed on the surface of the nano-alumina particles, thereby utilizing the effect of nano-alumina to effectively avoid the re-agglomeration of the stretched molecular chains, so that the stretched molecular chains are "spread" on the surface of the alumina particles. In the subsequent hydrothermal reaction process, thanks to the full stretching of the molecular chains and the reaction site provided by the high specific surface area of ​​the nano-alumina surface, not only the degree of reaction is improved, but also the reaction is uniform.

[0019] Finally, the alumina can be dissolved by acid washing and removed during the dialysis process. In this way, the residual nano-alumina can be prevented from affecting the performance of the quantum dot ink, and the purity of the lignin carbon quantum dots in the product can also be taken into account.

[0020] Furthermore, the nano-alumina particles are spherical particles, and the sphericity of the nano-alumina particles is 9.0-9.2; and the particle size distribution range of the nano-alumina particles is 10-30 nm.

[0021] During the research process, the inventors found that the use of nano-alumina particles with higher sphericity can make the above-mentioned reaction process more uniform and the performance of different batches of products will be more consistent; this is mainly because the spherical particles are relatively uniform at different angles, so the blasting material can be evenly dispersed when "spreading" on its surface; however, when the sphericity is higher, even greater than 9.2, its effect on improving the reaction is already very limited, and it will instead lead to higher nano-alumina manufacturing costs.

[0022] Furthermore, the nano-alumina dispersion also includes dopamine in an amount of 0.6-1.0% by weight of the nano-alumina particles.

[0023] By further introducing a small amount of dopamine on the surface of nano-alumina particles, on the one hand, dopamine can assist in the adsorption and fixation of lignin on the surface of nano-alumina particles during the processing, thereby avoiding the desorption of lignin after "spreading" during the processing; on the other hand, dopamine contains N element, and the doping of a certain amount of N element can further improve the optical properties of lignin quantum dots in ink;

[0024] As for the dosage of dopamine, if the dosage is too small, obviously, its adsorption capacity for lignin is limited. However, if the dosage is too large, it will cause the nano-alumina particles to agglomerate themselves, making it difficult to disperse them, which will also affect the subsequent spreading of lignin.

[0025] Furthermore, the preparation of the lignin carbon quantum dots also includes:

[0026] After the dealkalized lignin and water are mixed, they are allowed to stand and swell, and then kept at a pressure of 6.0-8.0MPa and a temperature of 180-220°C for 20-30 minutes, and then the pressure is instantly released to normal pressure to obtain the blasting material;

[0027] Ultrasonic dispersion of nano-alumina particles in water to obtain a nano-alumina dispersion, wherein the mass ratio of nano-alumina to water is 1:8-10;

[0028] The blasting material and nano-alumina dispersion were mixed in a mass ratio of 1:10-12, sheared and dispersed evenly, and then hydrothermally reacted at a temperature of 180-200°C for 10-12 hours. After the reaction was completed, acid washing was performed to dissolve and remove the nano-alumina, and then filtered with a 0.45μm microporous filter membrane to remove impurities, and then dialyzed in deionized water for 24-36 hours through a 1000da dialysis bag, and then vacuum freeze-dried to obtain lignin carbon quantum dots.

[0029] Furthermore, the solvent is prepared by compounding the following raw materials in parts by volume:

[0030] 8-10 parts of anhydrous ethanol, 18-20 parts of ethylene glycol, 25-30 parts of propylene glycol, 25-30 parts of deionized water;

[0031] Furthermore, the amount of the solvent used is 30-35 times the mass of the lignin carbon quantum dots.

[0032] Furthermore, the binder is any one of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and polyvinyl alcohol;

[0033] Furthermore, the amount of the binder used is 3-5% of the mass of the solvent.

[0034] Furthermore, the preparation of the lignin carbon quantum dots also includes:

[0035] The blasting material and the nano-alumina dispersion are mixed, and a sodium hypochlorite solution of 8-10% of the mass of the blasting material is added, and after shearing and dispersing evenly, a hydrothermal reaction is carried out at a temperature of 180-200° C. for 10-12 hours. After the reaction is completed, the nano-alumina is dissolved and removed by acid washing, and then filtered, dialyzed, and dried to obtain lignin carbon quantum dots;

[0036] Wherein, the mass fraction of the sodium hypochlorite solution is 4-8%.

[0037] A quantum dot ink for printing optical materials is prepared by adopting the above-mentioned preparation method. DETAILED DESCRIPTION

[0038] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0039] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0040] In the monodisperse hollow nanoparticles mentioned below, the specific meaning of hollow is that bubbles are introduced by using emulsifiers or the like during the preparation process, so that the inside of the particles is in a hollow state, as distinguished from a completely solid state.

[0041] Example 1

[0042] Preparation of lignin carbon quantum dots:

[0043] After the dealkalized lignin and water are mixed in a mass ratio of 1:3, the mixture is stirred with a stirrer at a speed of 100 r / min for 20 minutes, and then allowed to swell for 8 hours at room temperature to obtain a swollen material, which is then transferred to a gas explosion tank. After the pressure is kept at 6.0 MPa and the temperature is 220°C for 20 minutes, the pressure relief valve of the gas explosion tank is opened, and the pressure is instantly released to normal pressure to obtain an explosion material;

[0044] Ultrasonic dispersion of nano-alumina particles in water, and adding 0.6% dopamine by weight of the nano-alumina particles, specifically, using an ultrasonic frequency of 60 kHz and continuous ultrasonic dispersion for 15 minutes to obtain a nano-alumina dispersion, wherein the mass ratio of nano-alumina to water is 1:8;

[0045] The blasting material is mixed with the nano-alumina dispersion at a mass ratio of 1:10 while hot, and a sodium hypochlorite solution of 8% of the mass of the blasting material is added. After shearing and dispersion for 20 minutes at a shear rate of 5000r / min, it is transferred to a hydrothermal reactor and subjected to a hydrothermal reaction at a temperature of 180°C for 10 hours. After the reaction is completed, it is pickled with 8% hydrochloric acid by mass to dissolve and remove the nano-alumina, and then filtered with a 0.45μm microporous filter membrane to remove impurities, and then dialyzed in deionized water for 24 hours through a 1000da dialysis bag, and then vacuum freeze-dried for 8 hours at a pressure of 120Pa and a temperature of -30°C to obtain lignin carbon quantum dots;

[0046] The nano-alumina particles are spherical particles, and the sphericity of the nano-alumina particles is 9.0; and the particle size distribution range of the nano-alumina particles is 10-30nm;

[0047] The mass fraction of the sodium hypochlorite solution is 4%;

[0048] Ink preparation:

[0049] By weight: 8 parts of anhydrous ethanol, 18 parts of ethylene glycol, 25 parts of propylene glycol, and 25 parts of deionized water are mixed with a stirrer for 10 minutes to obtain a solvent;

[0050] Add a binder of 3% by mass of the solvent to the solvent, then stir and dissolve it with a stirrer at a speed of 200 r / min for 40 minutes, then add lignin carbon quantum dots according to the ratio of the mass of the solvent to 30 times the mass of the lignin carbon quantum dots, then ultrasonically disperse it for 60 minutes under the condition of an ultrasonic frequency of 120 kHz, and discharge the material to obtain quantum dot ink for printing optical materials;

[0051] The binder is carboxymethyl cellulose.

[0052] Example 2

[0053] Preparation of lignin carbon quantum dots:

[0054] After the dealkalized lignin and water are mixed in a mass ratio of 1:3, the mixture is stirred with a stirrer at a speed of 100 r / min for 20 minutes, and then allowed to swell for 8 hours at room temperature to obtain a swollen material, and then the swollen material is transferred to a gas explosion tank, and the pressure is kept at a pressure of 7.0 MPa and a temperature of 200°C for 25 minutes, and then the pressure relief valve of the gas explosion tank is opened to instantly release the pressure to normal pressure to obtain an explosion material;

[0055] Ultrasonic dispersion of nano-alumina particles in water, and adding 0.8% dopamine by weight of the nano-alumina particles, specifically, using an ultrasonic frequency of 70 kHz and continuous ultrasonic dispersion for 15 minutes to obtain a nano-alumina dispersion, wherein the mass ratio of nano-alumina to water is 1:9;

[0056] The blasting material is mixed with the nano-alumina dispersion at a mass ratio of 1:11 while hot, and a sodium hypochlorite solution of 9% of the mass of the blasting material is added. After shearing and dispersion for 25 minutes at a shear rate of 5500r / min, the mixture is transferred to a hydrothermal reactor and subjected to a hydrothermal reaction for 11 hours at a temperature of 190°C. After the reaction is completed, the mixture is pickled with 9% hydrochloric acid to dissolve and remove the nano-alumina, and then filtered with a 0.45μm microporous filter membrane to remove impurities, and then dialyzed in deionized water for 32 hours through a 1000da dialysis bag, and then vacuum freeze-dried for 10 hours at a pressure of 120Pa and a temperature of -30°C to obtain lignin carbon quantum dots.

[0057] The nano-alumina particles are spherical particles, and the sphericity of the nano-alumina particles is 9.1; and the particle size distribution range of the nano-alumina particles is 10-30nm;

[0058] The mass fraction of the sodium hypochlorite solution is 6%;

[0059] Ink preparation:

[0060] By weight: 9 parts of anhydrous ethanol, 19 parts of ethylene glycol, 28 parts of propylene glycol, and 28 parts of deionized water were mixed with a stirrer for 10 minutes to obtain a solvent;

[0061] Add a binder of 4% by mass of the solvent to the solvent, then stir and dissolve it with a stirrer at a speed of 200 r / min for 40 minutes, then add lignin carbon quantum dots to the solvent in a ratio of 32 times the mass of the lignin carbon quantum dots, then ultrasonically disperse it for 60 minutes at an ultrasonic frequency of 130 kHz, and discharge the material to obtain quantum dot ink for printing optical materials;

[0062] The binder is sodium carboxymethyl cellulose.

[0063] Example 3

[0064] Preparation of lignin carbon quantum dots:

[0065] After the dealkalized lignin and water are mixed in a mass ratio of 1:3, the mixture is stirred with a stirrer at a speed of 100 r / min for 20 minutes, and then allowed to swell for 8 hours at room temperature to obtain a swollen material, which is then transferred to a gas explosion tank. After the pressure is kept at 8.0 MPa and the temperature is 180°C for 30 minutes, the pressure relief valve of the gas explosion tank is opened, and the pressure is instantly released to normal pressure to obtain an explosion material;

[0066] Ultrasonic dispersion of nano-alumina particles in water, and addition of 1.0% dopamine by weight of the nano-alumina particles, specifically, an ultrasonic frequency of 80 kHz, and continuous ultrasonic dispersion for 15 minutes to obtain a nano-alumina dispersion, wherein the mass ratio of nano-alumina to water is 1:10;

[0067] The blasting material is mixed with the nano-alumina dispersion at a mass ratio of 1:12 while hot, and a sodium hypochlorite solution of 10% of the mass of the blasting material is added, and the mixture is sheared and dispersed for 30 minutes at a shear rate of 6000 r / min, and then transferred to a hydrothermal reactor, and the hydrothermal reaction is carried out at a temperature of 200°C for 12 hours. After the reaction is completed, the mixture is pickled with 10% hydrochloric acid to dissolve and remove the nano-alumina, and then filtered with a 0.45 μm microporous filter membrane to remove impurities, and then dialyzed in deionized water for 36 hours through a 1000da dialysis bag, and then vacuum freeze-dried for 12 hours at a pressure of 120 Pa and a temperature of -30°C to obtain lignin carbon quantum dots;

[0068] The nano-alumina particles are spherical particles, and the sphericity of the nano-alumina particles is 9.2; and the particle size distribution range of the nano-alumina particles is 10-30nm;

[0069] The mass fraction of the sodium hypochlorite solution is 8%;

[0070] Ink preparation:

[0071] By weight: take 10 parts of anhydrous ethanol, 20 parts of ethylene glycol, 30 parts of propylene glycol, and 30 parts of deionized water, and stir and mix them with a stirrer for 10 minutes to obtain a solvent;

[0072] Add a binder of 5% by mass of the solvent to the solvent, then stir and dissolve it with a stirrer at a speed of 200 r / min for 40 minutes, then add lignin carbon quantum dots to the solvent in a ratio of 35 times the mass of the lignin carbon quantum dots, then ultrasonically disperse for 60 minutes at an ultrasonic frequency of 150 kHz, and discharge the material to obtain quantum dot ink for printing optical materials;

[0073] The binder is hydroxyethyl cellulose.

[0074] Example 4

[0075] The difference between this embodiment and embodiment 1 is that dopamine is not added, and other conditions remain unchanged.

[0076] Example 5

[0077] Compared with Example 1, this embodiment differs in that sodium hypochlorite is not added, and other conditions remain unchanged.

[0078] Example 6

[0079] Compared with Example 1, this embodiment is different in that:

[0080] The sphericity of the nano-alumina particles is 8.6; and the particle size distribution range of the nano-alumina particles is 10-30 nm; and the other conditions remain unchanged.

[0081] Example 7

[0082] Compared with Example 1, this embodiment is different in that:

[0083] The sphericity of the nano-alumina particles is 9.0; and the particle size distribution range of the nano-alumina particles is 1-100 nm, and the other conditions remain unchanged.

[0084] Comparative Example 1

[0085] Compared with Example 1, this comparative example has the following differences:

[0086] No nano-alumina particles were added, and deionized water was used instead of the nano-alumina dispersion, while the other conditions remained unchanged.

[0087] Comparative Example 2

[0088] Compared with Example 1, this comparative example has the following differences:

[0089] Preparation of lignin carbon quantum dots:

[0090] The dealkalized lignin and water were mixed in a mass ratio of 1:3, stirred with a stirrer at a speed of 100 r / min for 20 min, and then allowed to swell at room temperature for 8 h to obtain a swelling material;

[0091] Ultrasonic dispersion of nano-alumina particles in water, and adding 0.6% dopamine by weight of the nano-alumina particles, specifically, using an ultrasonic frequency of 60 kHz and continuous ultrasonic dispersion for 15 minutes to obtain a nano-alumina dispersion, wherein the mass ratio of nano-alumina to water is 1:8;

[0092] The swelling material and the nano-alumina dispersion are mixed in a mass ratio of 1:10, and a sodium hypochlorite solution of 8% by mass of the swelling material is added, and the mixture is sheared and dispersed for 20 minutes at a shear rate of 5000 r / min, and then transferred to a hydrothermal reactor, and the hydrothermal reaction is carried out at a temperature of 180°C for 10 hours. After the reaction is completed, the mixture is pickled with 8% hydrochloric acid to dissolve and remove the nano-alumina, and then filtered with a 0.45 μm microporous filter membrane to remove impurities, and then dialyzed in deionized water for 24 hours through a 1000da dialysis bag, and then vacuum freeze-dried for 8 hours at a pressure of 120 Pa and a temperature of -30°C to obtain lignin carbon quantum dots;

[0093] The rest of the conditions remain unchanged.

[0094] The performance of the lignin carbon quantum dots obtained in the above examples and comparative examples was tested, and the specific test methods and test results are as follows:

[0095] Fluorescence quantum yield test of lignin carbon quantum dots:

[0096] Quinine sulfate was selected as a reference substance (quantum yield = 54.00%), and the fluorescence spectra and absorbance curves of the reference substance and the lignin carbon quantum dot solution sample were measured at an excitation wavelength of 360 nm, and the fluorescence quantum dot yield was calculated according to the following formula:

[0097] Fluorescent quantum dot yield = reference quantum dot yield × (I X / I R )×(A R / A X )×(M 2 / N 2 )

[0098] Among them, I Xis the integrated area of ​​the fluorescence spectrum of the lignin carbon quantum dot solution sample;

[0099] I R is the integrated area of ​​the fluorescence spectrum of the reference substance;

[0100] A R is the absorbance of the reference substance at an excitation wavelength of 360 nm;

[0101] A X is the absorbance of the lignin carbon quantum dot solution at an excitation wavelength of 360 nm;

[0102] M is the refractive index of lignin carbon quantum dots solution;

[0103] N is the refractive index of the reference material;

[0104] The specific test and calculation results are shown in Table 1;

[0105] According to the above test method, three groups of parallel samples were prepared using the preparation method of the embodiment or comparative example, and the fluorescence quantum yield of the parallel samples was tested respectively to evaluate the uniformity of sample performance between different batches;

[0106]

[0107]

[0108] It can be seen from the test results in Table 1 that the performance of the lignin carbon quantum dots obtained in the present invention is more uniform between different batches, and has a good fluorescence quantum yield, and can be applied to printed optical materials.

[0109] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing quantum dot ink for printing optical materials, characterized in that: The specific preparation steps include: Preparation of lignin carbon quantum dots: After the dealkalized lignin and water are mixed, they are allowed to stand and swell, and then they are kept at a pressure of 6.0-8.0MPa and a temperature of 180-220°C, and then the pressure is instantly released to normal pressure to obtain a blasting material; Ultrasonic dispersion of nano-alumina particles in water to obtain a nano-alumina dispersion; After the blasting material and the nano-alumina dispersion are evenly dispersed by shearing, the reaction is carried out at a temperature of 180-200°C for 10-12 hours. After the reaction is completed, the nano-alumina is dissolved and removed by acid washing, and then filtered, dialyzed, and dried to obtain lignin carbon quantum dots. Ink preparation: The lignin carbon quantum dots, solvent and binder are evenly dispersed to obtain quantum dot ink for printing optical materials.

2. The method for preparing a quantum dot ink for printing optical materials according to claim 1, characterized in that: The nano-alumina particles are spherical particles, and the sphericity of the nano-alumina particles is 9.0-9.2; and the particle size distribution range of the nano-alumina particles is 10-30 nm.

3. The method for preparing a quantum dot ink for printing optical materials according to claim 1, characterized in that: The nano-alumina dispersion also includes dopamine in an amount of 0.6-1.0% by weight of the nano-alumina particles.

4. The method for preparing a quantum dot ink for printing optical materials according to claim 1, characterized in that: The preparation of the lignin carbon quantum dots also includes: After the dealkalized lignin and water are mixed, they are allowed to stand and swell, and then kept at a pressure of 6.0-8.0MPa and a temperature of 180-220°C for 20-30 minutes, and then the pressure is instantly released to normal pressure to obtain the blasting material; Ultrasonic dispersion of nano-alumina particles in water to obtain a nano-alumina dispersion, wherein the mass ratio of nano-alumina to water is 1:8-10; The blasting material and nano-alumina dispersion were mixed in a mass ratio of 1:10-12, sheared and dispersed evenly, and then hydrothermally reacted at a temperature of 180-200°C for 10-12 hours. After the reaction was completed, acid washing was performed to dissolve and remove the nano-alumina, and then filtered with a 0.45μm microporous filter membrane to remove impurities, and then dialyzed in deionized water for 24-36 hours through a 1000da dialysis bag, and then vacuum freeze-dried to obtain lignin carbon quantum dots.

5. The method for preparing a quantum dot ink for printing optical materials according to claim 1, characterized in that: The solvent is prepared by compounding the following raw materials in parts by volume: 8-10 parts of anhydrous ethanol, 18-20 parts of ethylene glycol, 25-30 parts of propylene glycol, 25-30 parts of deionized water; Furthermore, the amount of the solvent used is 30-35 times the mass of the lignin carbon quantum dots.

6. The method for preparing a quantum dot ink for printing optical materials according to claim 1, characterized in that: The binder is any one of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose and polyvinyl alcohol; Furthermore, the amount of the binder used is 3-5% of the mass of the solvent.

7. The method for preparing a quantum dot ink for printing optical materials according to claim 1, characterized in that: The preparation of the lignin carbon quantum dots also includes: The blasting material and the nano-alumina dispersion are mixed, and a sodium hypochlorite solution of 8-10% of the mass of the blasting material is added, and after shearing and dispersing evenly, a hydrothermal reaction is carried out at a temperature of 180-200° C. for 10-12 hours. After the reaction is completed, the nano-alumina is dissolved and removed by acid washing, and then filtered, dialyzed, and dried to obtain lignin carbon quantum dots; Wherein, the mass fraction of the sodium hypochlorite solution is 4-8%.

8. A quantum dot ink for printing optical materials, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 7.